Pressure pain mapping for the investigation of mechanical sensitifity among elite male football players. Effects of turf type - Dominguez-Martin, M. A.; Lopez-Ruis, F.; Reyes-Lopez, M. V.; Valenza, G.; Fernandez de las Penas, C.; Madeleine, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Differences in muscle restitution between artificial turf and natural grass could induce muscle fatigue and, hence increase the risk of injury among football players (Ekstrand et al., 2010). The mechanical sensitivity of muscle is changed in response to strenuous physical activity or training (Kawcynski et al. 2012). Thus, studies investigating deep structures sensitivity can be helpful to delineate differences among pitch surfaces. In this study, we investigated if artificial grass compared with natural grass would affect the pressure pain maps of the lower extremity in elite football players. Methods: A total of 16 football players (mean age +/- SD: 22 +/- 2 years) for artificial turf and 13 football players (age: 22 +/- 3 years) for natural grass participated. Pressure pain thresholds (PPT) were measured bilaterally over 23 locations of the lower extremity, including the rectus femoris, tensor fasciae latae, vastus lateralis/medialis; external and internal hamstrings; tibialis anterior; peroneous; external and internal gastrocnemius, and soleus muscles, in a blinded design. Results: The ANOVA detected significant differences in PPT between groups and measurement points (P < 0.001), but not between sides (P = 0.804). Football players playing on natural grass exhibited lower PPT as compared to those players playing on artificial turf (P < 0.05). In addition, PPT over vastus medialis muscle was the lowest one (most sensitive) and significantly lower than PPT levels over the rectus femoris, external and internal hamstrings, tibialis anterior; peroneous, external and internal gastrocnemius, and soleus muscles (P < 0.01); whereas PPT over the rectus femoris was the highest one (least sensitive) and significantly higher than PPT levels vastus lateralis and medialis, tibialis anterior, peroneous; external/internal gastrocnemius, and soleus muscles (P < 0.01). Discussion: We showed the ability of topographical mapping of pressure sensitivity to reveal heterogeneous distribution of mechanical sensitivity among football players in relation to turf type. The higher PPT levels found among elite male football players on artificial turf compared with natural grass underlining decreased mechanical pain sensitivity could be considered as a positive trend in agreement with (Ekstrand et al., 2010). However, such differences may also have adverse effects, i.e. less efficient protective mechanism and prospective studies are needed to confirm our findings.